Persepsi dan Pendampingan Belajar Anak Oleh Orang Tua Di Masa Pandemi Covid- 19 - Dwi Handayani; Murtono Murtono (Jurnal Prakarsa Paedagogia, 2021)
The purpose of this study was to (1) Describe the parents' perceptions of the implementation of learning from home by students, (2) To analyze the role of parents in learning assistance for students, (3)  To analyze the factors that support and hinder parents in learning assistance for fifth-grade students of SDN Tegalarum 1 during the Covid-19 pandemic.Supporting factors for learning assistance by parents for learning from home: (1) the use of WhatsApp as a communication medium and a learning medium (2) The role of schools in providing guidance and consultation services for students and parents. As for the obstacles faced by parents during learning assistance at home: (1) cellphones are often brought to work while children at home do not have cell phones; (2) some parents don't have Android phones; (3) Many parents find it difficult about learning materials when accompanying children to learn; (3) additional internet quota fees; and (4) additional work for parents in accompanying children to learn.